MANAJEMEN KESISWAAN DALAM PEMBINAAN MINAT DAN BAKAT SISWA DI SMA YA BAKII 01 KESUGIHAN CILACAP - Mutoharoh (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
Student Management is one of the most important parts of the school management framework. Management of interest and talent development is an activity to regulate or manage innate abilities or potentials to be developed, maintained continuously accompanied by a sense of interest to know, have, learn and prove in learning activities, both academic and non-academic. The purpose of this study is to determine the process of student management activities in fostering student minut and bajat at SMA YA BAKII 01 Kesugihan, starting from planning, implementing, organizing to evaluating activities. The method used is a qualitative research method oriented to phenomena or field events obtained from observations, interviews and documentation. The results showed that student management activities in fostering student interests and talents at SMA YA BAKII 01 Kesugihan had been going well from the planning process to the evaluation.